Incidence of Thrombocytopenia in NICU and Its Association with Immature Platelet Fraction and Absolute Immature Platelet Count: A Cross-sectional Study - Saylee Jagtap; Amit Saxena; Shreya Bhate; Yasha Dedhia; Mumtaz Sharif; Shital Kolhe; Vijay Sonawane (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: Neonatal Thrombocytopenia (TCP) is frequently encountered in the Neonatal Intensive Care Unit (NICU), occurring either due to decreased production or increased destruction of platelets. This condition often leads to increased platelet transfusions in a NICU setting. Immature Platelet Fraction (IPF) and Absolute Immature Platelet Count (AIPC) are hypothesised to be surrogate markers of bone marrow activity and can help in differentiating between TCP caused by decreased production or increased destruction. Aim: To estimate the incidence of neonatal TCP in newborns admitted to a tertiary care NICU and to investigate the association of IPF percentage and AIPC values with the cause of TCP. Materials and Methods: This cross-sectional study was conducted in the Department of Paediatrics and Neonatology at Dr. D.Y. Patil Medical College, Navi Mumbai, Maharashtra, India, from April 2021 to May 2022. All 46 newborns admitted to the NICU with TCP were enrolled in the study. The total number of NICU admissions during the study period was used to calculate the incidence. The Complete Blood Count (CBC) with reticulocyte count and peripheral smear was examined using the impedance technique. The IPF and AIPC values were determined using an automated CBC counter based on flow cytometry principles. Statistical analysis was performed using the Chi-square test. Results: The study included a total of 46 neonates with TCP, with an incidence rate of 6.14%. Among the patients with TCP, 18 (39.13%) had mild, 17 (36.95%) had moderate, and 11 (23.91%) had severe TCP. The majority of neonates (21.7%) had a significant maternal history of Pregnancy Induced Hypertension (PIH). Of the neonates with TCP, 42 (91.3%) had high IPF and 4 (8.6%) had normal IPF. Regarding AIPC, 29 (63.04%) had normal values, 11 (23.91%) had high values, and 6 (13%) had low values. No significant association was found between IPF and AIPC values and the diagnosis of TCP in this study. Conclusion: The present study concludes that IPF and AIPC investigations cannot be recommended as markers to confirm the cause of TCP.